PRINCIPLES OF ORGANIZATIONAL AND TECHNOLOGICAL DESIGNING OF THE ROBOTIZED WELDING COMPLEXES - U.G. LUDMIRSKIY; М.V. SOLTOVETS; А.N. GRITSYNA (Advanced Engineering Research)
In our work we form the principles of organizational and technological design of robotized technological complexes for manufacturing large-scale, non-rigid, spatial structures with great number of short-length welding joints. The algorithm of design process is also considered.